Penerapan Penggunaan Aplikasi Akuntansi pada Usaha Mikro Home Industri (Studi Kasus Krupuk Ikan Haruan Nurhayati) - Hayati, Sari (Keizai, 2021)
Accounting is an information system that produces reports to interested parties regarding financial activities and business conditions. There are still many micro-enterprises as a support for the economy in Indonesia that have not yet implemented accounting applications in the preparation of financial statements to carry out all their activities. This study aims to determine the application of accounting applications and their benefits in the Haruan fish cracker business. The data used are primary and secondary obtained from interviews and evidence of recording during the 2020 period. The data analysis technique is qualitative descriptive. Constraints faced in implementing accounting applications include educational background, having never attended training in the application of accounting applications and internet networks. The results of this study are that the Haruan Fish Krupuk Business has prepared financial statements using the SME accounting application. The application greatly facilitates financial management, is time efficient, and is easy to control.